(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The article presents information about the change in the functional indicators of wrestlers in the process of physical training. The results obtained confirm the dependence of body weight and percentage of body fat on the physical development, physiometric and hemodynamic parameters of adolescent athletes, which can be used to assess the functional state and health status of an athlete in the pre-competitive period.